EM Design and Analysis of Dipole Arrays on Non-planar Dielectric Substrate - Singh, Hema; Chandini, R.; Jha, Rakesh Mohan (SpringerBriefs in Computational Electromagnetics,, 2016)
This book presents a simple and systematic description of EM design of antenna arrays. Printed dipole antennas are known to be simple yet more efficient than wire antennas. The dielectric substrate and the presence of ground plane affect the antenna performance and the resonant frequency is shifted. This book includes the EM design and performance analysis of printed dipole arrays on planar and cylindrical substrates. The antenna element is taken as half-wave centre-fed dipole. The substrate is taken as low-loss dielectric. The effect of substrate material, ground plane, and the curvature effect is discussed. Results are presented for both the linear and planar dipole arrays. The performance of dipole array is analyzed in terms of input impedance, return loss, and radiation pattern for different configurations. The effect of curved platform (substrate and ground plane) on the radiation behaviour of dipole array is analyzed. The book explains fundamentals of EM design and analysis of dipole antenna array through numerous illustrations. It is essentially a step-to-step guide for beginners in the field of antenna array design and engineering.